Characterization of the Visual Disability and Its Relation with the Resilience - CedeÃƒÂ±o, MarÃƒÂa Leonila GarcÃƒÂa; Rosado, Inger Solange Maitta; Loor, Karina Gissela Rivera (International Research Journal of Management, IT & Social Sciences, 2018)
The objective of the work is to determine the characterization of the visual disability and its relation with the resilience in the students of the Technical University of ManabÃ. The work shows an analysis of the visual disability in students and its impact on the level of resilience. An analysis of resilience is addressed regarding the physical and mental state of the people, as well as the process of adapting to the problems and adversities of life. The results are shown in tables and graph on the analysis of the degree of visual disability of the students, as well as the application of the SV-RES test prepared by the researchers Saavedra & Villalta, 2008. Based on the evaluation of 12 dimensions, which allow verifying the situation according to three scales: high, average and low. Finally, the conclusions are offered where the objective stated in the investigation is verified.